A selection of distinguished papers from the 19th Working Conference on Reverse Engineering 2012. Issue 11 (November 2014) - Oliveto, Rocco; Poshyvanyk, Denys; Oliveto, Rocco; Poshyvanyk, Denys
ABSTRACT This special issue contains a selection of distinguished papers from the 19th Working Conference on Reverse Engineering, held in Kingston, Ontario, Canada on October 15th–18th, 2012. The papers address a variety of topics related to reverse engineering, namely the analysis of execution traces, development of fast and efficient forward static slicing techniques, and mining of software repositories aiming at deriving novel patterns related to reverse engineering activities, such as the migration in Java libraries and the analysis of effects of file editing patterns on source code quality. Copyright © 2014 John Wiley & Sons, Ltd.